Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1001/archinternmed.2010.390
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Barber-Based Intervention for Improving Hypertension Control in Black Men

Abstract: Context Barbershop-based hypertension (HTN) outreach programs for black men are becoming increasingly common, but whether they are an effective approach for improving HTN control remains uncertain. Objective To evaluate whether a continuous high blood pressure (BP) monitoring and referral program conducted by barbers will motivate male patrons with elevated BP to pursue physician follow-up, leading to improved HTN control. Design, Setting, and Participants Cluster randomized trial (Barber-Assisted Reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 24 publications
4
145
1
Order By: Relevance
“…The median time between the home visit and clinic visit in the MH group was 2.30 months (IQR: 1.08 to 7.79 months), and we cannot exclude the possibility that treatment of hypertension between the home and clinic visits may have led to normalization of office BP and overdiagnosis of masked hypertension. However, previous studies have shown a very small percentage of participants in the community-based BP screening program received a new diagnosis of hypertension or treatment of hypertension after BP screening, unless additional medical or behavioral interventions were implemented (28)(29)(30)(31). The rates of progression to sustained hypertension among individuals with WCH and MH are also unknown because home BP was not measured during the follow-up study in the Dallas Heart Study (DHS-2).…”
Section: Discussionmentioning
confidence: 99%
“…The median time between the home visit and clinic visit in the MH group was 2.30 months (IQR: 1.08 to 7.79 months), and we cannot exclude the possibility that treatment of hypertension between the home and clinic visits may have led to normalization of office BP and overdiagnosis of masked hypertension. However, previous studies have shown a very small percentage of participants in the community-based BP screening program received a new diagnosis of hypertension or treatment of hypertension after BP screening, unless additional medical or behavioral interventions were implemented (28)(29)(30)(31). The rates of progression to sustained hypertension among individuals with WCH and MH are also unknown because home BP was not measured during the follow-up study in the Dallas Heart Study (DHS-2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in communities suffering from high rates of chronic disease, using community health workers, who are more fluent in the local culture and are familiar faces in the community, has proven to be an effective strategy in coping with hypertension and diabetes. 83 Furthermore, in a study of rural low-income women with diabetes, high cholesterol, or hypertension, community health workers improved healthy behaviors through setting small incremental individual goals with patients. 84 An important factor in that success may be that the community health workers focused the approaches to fit the appropriate goals for the local community given the available resources.…”
Section: Prescriptions For An Ailing Health Care Systemmentioning
confidence: 99%
“…3,4 Some approaches to addressing stroke disparities in African Americans have focused on improving risk factor awareness and control and increasing stroke literacy, which has been previously defined as the knowledge of stroke symptoms and risk factors. [5][6][7] Additional aspects of stroke literacy may include knowledge of treatment and appropriate stroke-related behavior.…”
mentioning
confidence: 99%